Cross-sectional Assessment of Body Image Perception, Image Satisfaction, Body Image Discrepancy and Dietary Habits in Medical Students of Ujjain - Rashmi Bhujade; Abhinav Sinha; Anupama Srivastva; Anil Singh Baghel (Wolters Kluwer Medknow Publications, 2024)
Background: Being judgmental about self-body image and satisfaction or dissatisfaction with one's own body is a natural phenomenon. If perceived incorrectly can lead to dissatisfaction and negative social, emotional, psychological and physical consequences. Methods: A cross-sectional study was planned and the data was collected with the help of a semi-structured proforma. Body image perception, image satisfaction, and associated dietary modification were inquired about, and Body Mass Index (BMI) and Body Image Discrepancy Score (BIDS) were calculated. The body image perception of participants was collected with the help of the Figure Rating Scale (FRS). Results: χ2 test, kappa statistics, Mann-Whitney test, multinominal regression, and Z-standardization were applied. Few 10% of participants perceived themselves as underweight, 48% as normal weight and 42% as overweight or obese. About 48%, 19%, and 33% of participants were satisfied, neutral and dissatisfied respectively by their perceived body image, and 43% of the participants had modified their diet. A statistically significant association was found between body image perception, image satisfaction, body image discrepancy and gender. Conclusion: There was a huge disagreement between perceived and actual body image. Overestimation and underestimation of body image were common in males and females respectively. Misperception of body image might lead to unnecessary dietary modifications resulting in malnutrition and somatoform disorders.